In Search of the Market Failure in the Asian Crisis - Karacadag, Cem; Samuels II, Barbara (Tufts Archival Research Center, 2005)
Volume 23, Issue 1. Winter/Spring The private sector's inadequate country risk analysis is at the heart of the crisis. This led to high-risk cross-border lending and investment in the region as the market lacked the information it required to function properly.